Diagnostic Accuracy of Real-Time Shear Wave Elastography for Staging of Liver Fibrosis: A Meta-Analysis - Li, Changtian (Med Sci Monit, 2016)
BACKGROUND: The present meta-analysis, based on previous studies, was aimed to evaluate the test accuracy of real-time shear wave elastography (SWE) for the staging of liver fibrosis. MATERIAL/METHODS: A systematic search on MEDLINE, PubMed, Embase, and Google Scholar databases was conducted, and data on SWE tests and liver fibrosis staging were collected. For each cut-off stage of fibrosis (F≥2, F≥3, and F≥4), pooled results of sensitivity, specificity, and area under summary receiver operating characteristic (SROC) curve were analyzed. The study heterogeneity was evaluated by χ(2) and I(2) tests. I(2)>50% or P≤0.05 indicates there was heterogeneity, and then a random-effects model was applied. Otherwise, the fixed-effects model was used. The publication bias was evaluated using Deeks funnel plots asymmetry test and Fagan plot analysis was performed. RESULTS: Finally, 934 patients from 8 published studies were included in the analysis. The pooled sensitivity and specificity of SWE for F≥2 were 85.0% (95% CI, 82–88%) and 81% (95% CI, 71–88%), respectively. The area under the SROC curve with 95% CI was presented as 0.88 (95% CI, 85–91%). The pooled sensitivity and specificity of SWE for F≥3 were 90.0% (95% CI, 83.0–95.0%) and 81.0% (95% CI, 75.0–86.0%), respectively, corresponding to an area of SROC of 0.94 (95% CI, 92–96%). The pooled sensitivity and specificity of SWE for F≥4 were 87.0% (95% CI, 80.0–92.0%) and 88.0% (95% CI, 80.0–93.0%), respectively, corresponding to an area of SROC of 0.92 (95% CI, 89–94%). CONCLUSIONS: The overall accuracy of SWE is high and clinically useful for the staging of liver fibrosis. Compared to the results of meta-analyses on other tests, such as RTE, TE, and ARFI, the performance of SWE is nearly identical in accuracy for the evaluation of cirrhosis. For the evaluation of significant liver fibrosis (F≥2), the overall accuracy of SWE seems to be similar to ARFI, but more accurate than RTE and TE.